Answer:
x = 6
y = 7
Explanation:
Here, (10x - 8y = 4) and (- 5x + 3y = - 9) are two given equation
Now, Name the equation
10x - 8y = 4
take 2 as common we get
2(5x - 4y = 2)
5x - 4y = 2 ...(1)
- 5x + 3y = - 9 ...(2)
Now, Subtract (1) from (2)
5x - 4y = 2
- 5x + 3y = - 9
————————
- y = - 7
y = 7
Now, Put the value of y in equation (1) we get
5x - 4y = 2
5x - 4(7) = 2
5x - 28 = 2
5x = 28 + 2
5x = 30
x = 30÷5
x = 6
Thus, The value of x is 6 and y is 7
FOR VERIFICATION ONLY:
5x - 4y = 2
5(6) - 4(7) = 2
30 - 28 = 2
2 = 2
- 5x + 3y = - 9
- 5(6) + 3(7) = - 9
- 30 + 21 = - 9
- 9 = - 9
Hence, L.H.S = R.H.S
-TheUnknownScientist